Rare bird documentation form for Greater Scaup at Volga River Recreation Area, 1983 - Moore, Francis L.et al (1983)
Rare bird documentation form for three Greater Scaups at Volga River Recreation Area in Fayette County, IA on November 25, 1983. Epson - sheet feed